2016
DOI: 10.1097/md.0000000000003058
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Small-Fiber Sensory System in Parkinson's Disease

Abstract: Sensory symptoms are frequent nonmotor complaints in patients with Parkinson's disease (PD). However, few investigations integrally explored the physiology and pathology of the thermonociceptive pathway in PD. We aim to investigate the involvement of the thermonociceptive pathway in PD.Twenty-eight PD patients (16 men, with a mean age and standard deviation of 65.6 ± 10.7 years) free of neuropathic symptoms and systemic disorders were recruited for the study and compared to 23 age- and gender-matched control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
1
27
0
2
Order By: Relevance
“…Morphologically, we did not detect overt signs of neuronal death or damage in DRGs of Pink1SNCA mice, but it has been shown that the density of sensory fiber terminals in the skin is reduced in PD patients [15,58], which is not a specific observation for PD associated sensory neuropathies but occurs frequently in sensory neuropathies associated with metabolic diseases such as diabetes mellitus [62]. The similarities suggests that metabolic dysfunctions of sensory neurons, which are not…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Morphologically, we did not detect overt signs of neuronal death or damage in DRGs of Pink1SNCA mice, but it has been shown that the density of sensory fiber terminals in the skin is reduced in PD patients [15,58], which is not a specific observation for PD associated sensory neuropathies but occurs frequently in sensory neuropathies associated with metabolic diseases such as diabetes mellitus [62]. The similarities suggests that metabolic dysfunctions of sensory neurons, which are not…”
Section: Discussionmentioning
confidence: 59%
“…They develop a progressive loss of thermal sensation far earlier than the earliest occurrence of clinical motor dysfunctions. The sensory phenotype is reminiscent of QST phenotypes of PD patients, which presents with a predominant loss of thermal sensation and preservation of mechanical sensitivity or mechanical hypersensitivity [18,58]. Pink1SNCA mice replicate the thermal versus mechanical dichotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found reduced thermal detection thresholds after STN-DBS (Deep Bran Stimulation of the Subthalamic Nucleus) [3,11,14,16,20,21], suggesting that central pathology plays a role in abnormal thermal sensation. Peripheral deafferentation probably also plays a role [15,17], as small ber neuropathy has been con rmed on skin biopsies in PD patients [6,7].…”
Section: Introductionmentioning
confidence: 95%
“…Only a limited number of studies have investigated thermal abnormalities in PD [11][12][13][14][15][16][17][18][19] and the underlying pathophysiology still remains unclear. Most of the published studies found increased thermal detection thresholds but no responsiveness to levodopa, suggesting that thermal abnormalities do not depend on dopaminergic de cit.…”
Section: Introductionmentioning
confidence: 99%
“…Intraepidermal nerve fibre density (IENFD) is the gold standard measure to quantify loss of skin innervation to diagnose a small fibre neuropathy (SFN) [5]. Several studies have demonstrated a significant reduction in IENFD in patients with PD [6][7][8]. These studies utilised immunostaining with the pan-axonal marker protein gene product 9.5 (PGP9.5).…”
mentioning
confidence: 99%